Lights and shadows on the use of metformin in pregnancy: from the preconception phase to breastfeeding and beyond - Tosti, Giulia; Barberio, Annarita; Tartaglione, Linda; Rizzi, Alessandro; Di Leo, Mauro; Viti, Luca; Sirico, Angelo; De Carolis, Sara; Pontecorvi, Alfredo; Lanzone, Antonio; Pitocco, Dario (Frontiers in Endocrinology, 2023)
During pregnancy the complex hormonal changes lead to a progressive decrease of insulin sensitivity that can drive to the onset of gestational diabetes (GDM) or worsen an already-known condition of insulin resistance like type 2 diabetes, polycystic ovarian syndrome (PCOS) and obesity, with complications both for the mother and the fetus. Metformin during pregnancy is proving to be safe in a growing number of studies, although it freely crosses the placenta leading to fetal level similar to maternal concentration. The aim of this literature review is to analyze the main available evidence on the use of metformin during, throughout, and beyond pregnancy, including fertilization, lactation and medium-term effects on offspring. Analyzed studies support the safety and efficacy of metformin during pregnancy. In pregnant women with GDM and type 2 diabetes metformin improves obstetric and perinatal outcomes. There is no evidence that it prevents GDM in women with pregestational insulin resistance or improves lipid profile and risk of GDM in pregnant women with PCOS or obesity. Metformin could have a role in reducing the risk of preeclampsia in pregnant women with severe obesity, the risk of late miscarriages and preterm delivery in women with PCOS and the risk of Ovarian Hyperstimulation Syndrome, increasing the clinical pregnancy rate in women with PCOS undergoing in vitro fertilization (IVF/FIVET). Offspring of mothers with GDM exposed to metformin have no significant differences in body composition compared with insulin treatment, while it appears to be protective for metabolic and cardiovascular risk.